Effect of Aslagh Capsule, a Traditional Compound Herbal Product on Oligomenorrhea in Patients with Polycystic Ovary Syndrome: A Three-Arm, Open-label, Randomized, Controlled Trial: - Bahman, Maryam; Hajimehdipoor, Homa; Bioos, Soodabeh; Hashem-Dabaghian, Fataneh; Afrakhteh, Maryam; Tansaz, Mojgan (Galen Medical Journal, 2019)
Background: Oligomenorrhea is a common complaint in patients with polycystic ovary syndrome (PCOS). There are some useful medicinal recommendations such as Aslagh product (include fennel fruits, carrot seeds, chaste tree fruits) in Iranian traditional medicine for the treatment of oligomenorrhea in PCOS. Hence, the present investigation was designed to compare Aslagh capsule with metformin on the oligomenorrhea. Materials and Methods: One hundred fifty women aged between 18-43 years with oligomenorrhea due to PCOS were randomly divided into Aslagh, metformin, and Aslagh + metformin groups. The occurrence of menstrual bleeding was considered as the primary outcome. Menstrual cyclicity, duration, and volume of the bleeding were also evaluated. Results: Occurrence of menstrual bleeding was 87.2% in all patients, with no significant difference between the three groups (P> 0.05). Menstrual cyclicity significantly improved from baseline in Aslagh and Aslagh+ metformin groups (P=0.02). Duration of menstrual bleeding was significantly higher in Aslagh group in the first and the second menstrual bleeding cycle compared to the other two groups (P<0.05). No significant change was observed in the volume of the bleeding after the intervention in any of the three groups. The occurrence of menstrual bleeding in Aslagh group was significantly (P=0.03) higher than the other two groups in the fourth month (drug-free period). Conclusion: Aslagh capsule showed beneficial effects similar to metformin in the treatment of oligomenorrhea in PCOS women and could be suggested for use as an alternative treatment in these patients. [GMJ.2019;8:e1261]